135k views
3 votes
If f(x)=x over 2-3 and g(x)=3x^2+x-6 find (f+g)(x)

2 Answers

4 votes

Answer:


(f + g) (x) =3x^(2) +(3)/(2)x-9

Explanation:

We are given the following two functions and we are to add them:


f (x) = \frac {x} {2} -3


g (x) = 3x^(2) + x - 6

Adding these two functions, we get:


(f + g) (x) = f (x) + g (x)


(f + g) (x) = \frac {1} {2} x - 3 + 3x^(2) + x - 6

Adding the like terms together and simplifying them to get:


(f + g) (x) = 3x^(2) + \frac {3}{2} x - 9

User Jrib
by
5.5k points
4 votes

Answer:


(f + g)(x) = 3x ^ 2 + (3)/(2)x - 9

Explanation:

We are asked to find (f + g) (x)

In this case what we must do is add the function f (x) with the function g (x). So, we have:


f(x) = (1)/(2)x - 3\\g (x) = 3x ^ 2 + x - 6\\(f + g) (x) = f(x) + g (x)\\(f + g) (x) = (1)/(2)x - 3 + 3x ^ 2 + x - 6

Finally we simplify, and we have left:


(f + g)(x) = 3x ^ 2 + (3)/(2)x - 9


User CBaker
by
6.1k points